We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
116
1
avatar

Solve the following equation for x

 

6(y+1) = 7(x-2) 

 

 

Thankyi

 May 15, 2019

Best Answer 

 #1
avatar+8724 
+3

\(6(y + 1) \,=\, 7(x - 2)\)

                                               Divide both sides of the equation by  7 .

\(\frac67(y + 1)\, =\, x - 2\)

                                               Add  2  to both sides of the equation.

\(\frac67(y + 1)+2\, =\, x\)

                                               We could stop here, but let's simplify it.

\(x\,=\,\frac67(y + 1)+2\)

                                               Distribute  \(\frac67\)  to the terms in parenthesees.

\(x\,=\,\frac67y + \frac67+2\)

                                               Add  \(\frac67+2\)

\(x\,=\,\frac67y + \frac67+\frac{14}{7}\\~\\ x\,=\,\frac67y + \frac{20}{7}\)

.
 May 15, 2019
 #1
avatar+8724 
+3
Best Answer

\(6(y + 1) \,=\, 7(x - 2)\)

                                               Divide both sides of the equation by  7 .

\(\frac67(y + 1)\, =\, x - 2\)

                                               Add  2  to both sides of the equation.

\(\frac67(y + 1)+2\, =\, x\)

                                               We could stop here, but let's simplify it.

\(x\,=\,\frac67(y + 1)+2\)

                                               Distribute  \(\frac67\)  to the terms in parenthesees.

\(x\,=\,\frac67y + \frac67+2\)

                                               Add  \(\frac67+2\)

\(x\,=\,\frac67y + \frac67+\frac{14}{7}\\~\\ x\,=\,\frac67y + \frac{20}{7}\)

hectictar May 15, 2019

22 Online Users

avatar